Reasons related to tooth loss among adolescents in São Paulo, Brazil - Luísa Helena Nascimento Tôrres; Juliana Zanatta; Raquel Aparecida Pizolato; Cássia Maria Grillo; Antônio Carlos Frias; Maria da Luz Rosário de Sousa (Universidade Estadual de Campinas, 2015)
Aim: To estimate tooth loss prevalence among adolescents in São Paulo, considering socioeconomic and demographic factors, dental service use and pain. Methods: Data were obtained from the São Paulo Oral Health Survey 2008. The sample comprised 2858 adolescents from 15 to 19 years old from public and private schools, who underwent through an oral examination. In addition, a questionnaire was applied regarding the characterization of factors related to socioeconomics, demographics, use of dental services and pain in the last six months. At least one tooth lost was the outcome. The independent variables included gender, ethnicity, parents' schooling, type of school, number of rooms, people and cars per home, family income, dental service use, decayed teeth, toothache. A multivariate logistic regression model was used. Results: The prevalence of tooth loss was 7%. The independent variables decayed tooth (RP=1.71), toothache (RP=2.04), father's schooling - elementary (RP=1.40) and per capita family income - less than 1/ 2 a minimum salary (RP=1.45) were associated with the outcome. Conclusions: The results suggest that socioeconomic factors may contribute to the increase of early tooth loss among adolescents.